A sodium metal negative electrode and its preparation method and application

By using UiO-66 high-temperature calcination in sodium metal batteries, the porous carbon material is compounded with selenium powder, and mixed with molten sodium to form Na@PC/Na2Se negative electrode, the dendrite formation and instability caused by the high reactivity of the negative electrode of sodium metal batteries is solved, and long-life cycle stability is achieved under high current density and high capacity.

CN119324205BActive Publication Date: 2025-03-18ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411857229.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Due to the high reactivity of sodium metal negative electrode, the formation of dendrites, unstable solid electrolyte interface and volume changes, resulting in fast capacity decay, low Coulomb efficiency and safety risks, limiting its actual deployment and application.

Method used

The porous carbon material obtained by high-temperature calcination of UiO-66 is mixed with selenium powder, calcined at high temperature and mixed with molten sodium and rolled to form the sodium metal negative electrode Na@PC/Na2Se. The negative electrode has a dual surface layer structure, the lower layer is a 3D porous carbon matrix, and the upper layer is an in-situ artificial Na2Se SEI layer, providing double protection.

Benefits of technology

The long-life cycle stability of sodium metal anode under high current density and high capacity conditions is achieved, dendrite growth is avoided, mechanical toughness and sodium philtrum are improved, and electrochemical properties are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324205B_ABST
    Figure CN119324205B_ABST
Patent Text Reader

Abstract

The present invention relates to a sodium metal negative electrode and a preparation method and application thereof, belonging to the technical field of battery materials. The preparation method of the sodium metal negative electrode of the present invention comprises the following steps: (1) mixing a solid obtained by high-temperature calcination of UiO-66 with a hydrofluoric acid solution, standing, and drying to obtain a porous carbon material; (2) mixing the porous carbon material obtained in step (1) with selenium powder, calcining at high temperature to obtain a selenium-porous carbon composite material; (3) uniformly mixing the selenium-porous carbon composite material obtained in step (2) with molten sodium, and rolling after cooling to obtain the sodium metal negative electrode. The negative electrode Na@PC / Na2Se of the present invention has a double surface layer, the lower layer comprises a 3D porous carbon matrix, and the upper layer is composed of a Na2Se SEI layer. This double protective intermediate layer enables the sodium metal negative electrode to obtain high mechanical toughness, excellent sodium affinity, and high ionic conductivity that adapt to volume changes, and realizes uniform high-rate Na deposition without dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a sodium metal negative electrode and a preparation method and application thereof. Background Art

[0002] Due to the scarcity and high cost of lithium resources, there has been great interest in cost-effective sodium secondary batteries to meet the growing demand for large-scale energy storage devices. Sodium-based batteries, including sodium metal batteries, sodium-air batteries, sodium-ion batteries, and sodium-sulfur batteries, have been explored as promising options for power grids and electric vehicles.

[0003] The high reactivity of sodium metal anode (SMA) constantly causes some undesirable challenges, such as uncontrolled dendrite formation, unstable solid electrolyte interface (SEI), and large volume changes during cycling, which further consume excess electrolyte and form “dead Na” metal, which lead to fast capacity decay, low Coulombic efficiency and potential safety risks, thus hindering the practical deployment of sodium metal batteries (SMBs).

[0004] To overcome the above problems, various strategies for stable manipulation of sodium metal batteries have been proposed, including in situ formation of solid electrolyte interface (SEI) film by adding electrolyte additives, preparation of alkali alloys (NaBi, NaSn, Na3P), alkali chlorides (NaF, NaBr, NaI), etc. as protective layers on the sodium surface to stabilize the electrode-electrolyte interface. The purpose of these modifications is to create an artificial SEI layer without changing the structure or surface chemical properties of sodium metal. However, these methods have limited performance at low areal current densities (<2 mA cm −2 ) and surface capacity (<1mAhcm −2 ), but still cannot achieve long life at high surface current density and surface capacity. Therefore, further electrode modification methods are urgently needed to mass-produce sodium metal batteries with high stability and safety. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a sodium metal negative electrode and a preparation method and application thereof.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a sodium metal negative electrode, comprising the following steps:

[0008] (1) The solid obtained by high-temperature calcination of UiO-66 is mixed with a hydrofluoric acid (HF) solution, allowed to stand, and dried to obtain a porous carbon material (PC);

[0009] (2) mixing the porous carbon material obtained in step (1) with selenium (Se) powder, and calcining at high temperature to obtain a selenium-porous carbon composite material (PC@Se);

[0010] (3) The selenium-porous carbon composite material obtained in step (2) is uniformly mixed with molten sodium, and the mixture is rolled after cooling to obtain the sodium metal negative electrode (Na@PC / Na2Se).

[0011] In the preparation method of the sodium metal negative electrode of the present invention, UiO-66MOF is used as a raw material to prepare a porous structure, and the formula unit of UiO-66 is composed of 1,4-dicarboxybenzene (H2BDC) as an organic linker, Zr6O4(OH)4(CO2) 12 It is composed of structural building units (SBU). The present invention first calcines UiO-66 at high temperature, and the thermal decomposition of carboxylic acid groups during calcination causes SBU to be in situ transferred to ZrO2, and then etches with HF solution to increase the surface reaction area to obtain a porous carbon material (PC); and then Se particles are uniformly decorated on the surface of the porous carbon material through a solid phase reaction to obtain a selenium-porous carbon composite material (PC@Se). Finally, the composite material is fully mixed with molten sodium, and rolled after cooling to obtain a sodium metal negative electrode. In the Na@PC / Na2Se negative electrode obtained by the present invention, PC can directly contact the metal surface, and during the molten mixing and rolling process, the attraction between Na metal and Se atoms produces an in-situ artificial Na2Se layer, so that the negative electrode Na@PC / Na2Se of the present invention has a double surface layer, the lower layer contains a 3D PC matrix, and the upper layer is composed of a Na2Se SEI layer. This double protective intermediate layer enables the sodium metal negative electrode to obtain high mechanical toughness, excellent sodium affinity and high ionic conductivity that adapt to volume changes, and realizes uniform high-rate Na deposition without dendrites.

[0012] Preferably, in step (1), the preparation method of UiO-66 comprises the following steps: dissolving zirconium chloride (ZrCl4), terephthalic acid (H2BDC) and acetic acid in dimethylformamide (DMF), and then performing a hydrothermal reaction to obtain UiO-66.

[0013] Specifically, in the preparation method of UiO-66, the mass volume ratio of zirconium chloride, terephthalic acid and acetic acid is (40-60) mg: (30-50) mg: (4-8) mL; the temperature of the hydrothermal reaction is 100°C-140°C, and the time is 12h-20h; after the hydrothermal reaction, centrifugation, washing and drying are performed to obtain UiO-66.

[0014] Preferably, in step (1), the high temperature calcination is carried out at a temperature of 750°C-850°C, for a time of 3h-5h, and at a heating rate of 4.5°C / min-5.5°C / min.

[0015] Preferably, in step (1), the mass volume ratio of the solid to the hydrofluoric acid solution is (50-150) mg: (20-60) mL; and the mass percentage of hydrofluoric acid in the hydrofluoric acid solution is 5%-7%.

[0016] Preferably, in step (1), the standing time is 1 h to 3 h.

[0017] Preferably, in the step (1), the solution is centrifuged, washed and dried after standing to obtain a porous carbon material; the drying temperature is 70° C.-90° C. and the drying time is 10 h-14 h.

[0018] Preferably, in the step (2), the mass ratio of the porous carbon material to the selenium powder is 1:(3-10).

[0019] More preferably, in the step (2), the mass ratio of the porous carbon material to the selenium powder is 1:(4.5-5.5).

[0020] Preferably, in step (2), the high temperature calcination is carried out at a temperature of 800°C-900°C, for a time of 3h-5h, and at a heating rate of 4.5°C / min-5.5°C / min.

[0021] Preferably, in step (1) and step (2), the high-temperature calcination is carried out in an inert atmosphere, and the inert atmosphere includes argon.

[0022] Preferably, in step (3), the mass ratio of the selenium-porous carbon composite material to the molten sodium is (8-12):1.

[0023] Preferably, in step (3), the temperature of the molten sodium is 200°C-300°C.

[0024] Preferably, in the step (3), the mixing is performed by stirring, and the stirring time is 30 min-60 min.

[0025] Preferably, the step (3) is performed in an inert atmosphere, and the inert atmosphere comprises argon.

[0026] Preferably, in the step (3), the rolling is performed 5-15 times.

[0027] In the step (3), there is no restriction on the temperature after cooling down. For example, the temperature can be cooled down to room temperature (15°C-35°C) to be able to carry out the next step of rolling.

[0028] In a second aspect, the present invention provides a sodium metal negative electrode prepared by the method for preparing the sodium metal negative electrode.

[0029] In a third aspect, the present invention provides a sodium metal battery, comprising the sodium metal negative electrode.

[0030] The battery comprising the sodium metal negative electrode of the present invention has excellent electrochemical performance and has a long cycle life at high current density and areal capacity.

[0031] The present invention has the following beneficial effects: the present invention prepares a three-dimensional porous scaffold PC@Se, which forms a dual-functional mixed interface layer on the surface of Na metal during the mixing and rolling process with molten sodium. In the Na@PC / Na2Se electrode of the present invention, the lower layer contains PC that can directly contact the metal surface, and the upper layer contains an in-situ artificial Na2Se layer. In the initial process, the in-situ Na2Se artificial SEI layer can provide a more uniform and mechanically stable host for the controlled growth of Na metal. The 3D matrix of PC as a support on the Na metal surface can further adapt to the volume expansion of the interface and promote the reversibility of the Na2SeSEI layer during repeated plating / stripping. This synergistic effect makes Na + Under high current density and high capacity conditions, it can also migrate uniformly and quickly to the artificial layer without dendrite growth, so that the electrode of the present invention has excellent electrochemical performance and long cycle life under high current density and surface capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The electron microscope images of PC and PC@Se in Example 1, wherein (a) is the SEM image of PC, (b) is the TEM image of PC, (c) is the SEM image of PC@Se, and (d) is the TEM image of PC@Se;

[0033] Figure 2 The electrochemical performance test results of carbonate-based electrolyte symmetric batteries are shown in Figure 1, where (a) shows the electrochemical performance of bare Na, Na@PC of Comparative Example 1, Na@Se of Comparative Example 2, and Na@PC / Na2Se symmetric batteries of Example 1 at 1 mA cm −2 Up to 1mAh cm −2 (a) is the cycle performance diagram of the Na@PC / Na2Se symmetric battery of Example 1, (b) is the EIS spectrum of the Na@PC / Na2Se symmetric battery of Example 1, and (c) is a statistical diagram comparing the cycle performance of Example 1 with that of the existing literature;

[0034] Figure 3 The cycle performance diagrams of the sodium metal negative electrode of Examples 4 and 5 in carbonate-based electrolytes, wherein (a) is the symmetrical battery of Example 4 at 1 mA cm −2 Up to 1mAh cm −2 (b) is the cycle performance diagram of the symmetrical battery of Example 5 at 1 mA cm −2 Up to 1mAh cm −2 Cyclic performance diagram at capacity;

[0035] Figure 4 The electrochemical performance test results of ether electrolyte symmetric batteries, where (a) is the Na@PC / Na2Se symmetric battery of Example 1 at 5 mA cm −2 Up to 2.5 mAh cm −2 (a) is a long cycle performance diagram, and (b) is a statistical diagram comparing the cycle performance of Example 1 with that of the existing literature;

[0036] Figure 5 The ether electrolyte symmetric battery assembled from bare Na, Comparative Example 1, and Comparative Example 2 was 4 mAcm −2 Up to 0.5 mAhcm −2 Cyclic performance diagrams of , where (a) is bare Na, (b) is comparative example 2, and (c) is comparative example 1;

[0037] Figure 6 The electrochemical performance test results of the full battery prepared with bare Na and Example 1 as the negative electrode, wherein (a) is a long cycle performance diagram at 5C, and (b) is a long cycle performance diagram at 20C;

[0038] Figure 7 The electrochemical performance test results of the asymmetric battery are shown in Figure 1, wherein (a) is the initial nucleation overpotential of sodium deposition in the asymmetric battery of bare Na, Na@PC of Comparative Example 1, Na@Se of Comparative Example 2, and Na@PC / Na2Se of Example 1, and (b) is the coulombic efficiency of the bare Na, Na@PC of Comparative Example 1, Na@Se of Comparative Example 2, and Na@PC / Na2Se electrodes in the asymmetric battery;

[0039] Figure 8 Surface morphology of the Na@PC / Na2Se electrode and the bare Na electrode of Example 1, wherein (ad) are scanning electron microscope (SEM) images of the bare Na after 100 cycles, (eh) are scanning electron microscope (SEM) images of the Na@PC / Na2Se electrode of Example 1 after 100 cycles, (i) is an optical microscope image of the bare Na, and (j) is an optical microscope image of the Na@PC / Na2Se electrode of Example 1 during the electroplating process;

[0040] Fig. 9 Schematic diagram of the structure of the PC@Se composite material of the present invention and a schematic diagram of the principle of in-situ artificial SEI layer modification of the Na electrode. DETAILED DESCRIPTION

[0041] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0042] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0043] Example 1

[0044] A method for preparing a sodium metal negative electrode comprises the following steps:

[0045] (1) UiO-66 was placed in a porcelain boat, and then heated to 800 °C at a heating rate of 5 °C / min in an argon atmosphere in a tube furnace. The solid (ZrO2@C) was obtained. Then 100 mg of the obtained solid was dispersed in 40 mL of distilled water containing 6 mL of HF solution (HF 40% w / w) and ultrasonicated for 30 min. After ultrasonic treatment, the solution was allowed to stand for 2 h until the temperature dropped to room temperature. It was centrifuged again at 9000 rpm for 5 min, washed twice with methanol and once with distilled water, and finally heated in an oven at 80 °C for 12 h to obtain a porous carbon material (PC).

[0046] (2) The porous carbon material obtained in step (1) and selenium (Se) powder were mixed in a mass ratio of 1:5, placed in a porcelain boat, and then heated to 850°C in a tube furnace in an argon atmosphere at a heating rate of 5°C / min and calcined for 4 hours to obtain a selenium-porous carbon composite material (PC@Se);

[0047] (3) In an argon-filled glove box (O2 and H2O <0.1 ppm), sodium metal was heated at 250°C, and then the selenium-porous carbon composite material powder obtained in step (2) was slowly added, with the mass ratio of selenium-porous carbon composite material to molten sodium being 10:1. The mixture was stirred for 40 minutes, and the temperature was lowered to room temperature before rolling for 10 times to obtain the sodium metal anode (Na@PC / Na2Se).

[0048] The preparation method of UiO-66 in step (1) comprises the following steps: dissolving 37.5 mg H2BDC and 52.5 mg ZrCl4 in 50 mL DMF containing 6 mL glacial acetic acid (HAc), then ultrasonically treating the mixed solution for 40 min, sealing it and placing it in a 120°C oven for hydrothermal reaction for 16 h, and finally centrifuging it at 9000 rpm for 10 min, washing it 3 times with a mixture of DMF and methanol (v / v 1:4), and drying it in a vacuum oven at 80°C for 12 h to obtain the UiO-66.

[0049] Example 2

[0050] A method for preparing a sodium metal negative electrode comprises the following steps:

[0051] (1) UiO-66 was placed in a porcelain boat, and then heated to 850°C at a heating rate of 5°C / min in a tube furnace in an argon atmosphere for 3 hours to obtain a solid (ZrO2@C). 50 mg of the obtained solid was dispersed in 40 mL of distilled water containing 6 mL of HF solution (HF40% w / w) and maintained for 30 minutes of ultrasonic treatment. After ultrasonic treatment, the solution was allowed to stand for 1 hour until the temperature dropped to room temperature, and then centrifuged again at 9000 rpm for 5 minutes, washed twice with methanol and once with distilled water, and finally heated in an oven at 80°C for 12 hours to obtain a porous carbon material (PC);

[0052] (2) The porous carbon material obtained in step (1) and selenium (Se) powder were mixed in a mass ratio of 1:4.5, placed in a porcelain boat, and then heated to 800°C in a tube furnace in an argon atmosphere at a heating rate of 5°C / min and calcined for 5h to obtain a selenium-porous carbon composite material (PC@Se);

[0053] (3) In an argon-filled glove box (O2 and H2O <0.1 ppm), sodium metal was heated at 250°C, and then the selenium-porous carbon composite material powder obtained in step (2) was slowly added, with the mass ratio of selenium-porous carbon composite material to molten sodium being 8:1. The mixture was stirred for 40 minutes, and the temperature was lowered to room temperature before rolling for 10 times to obtain the sodium metal anode (Na@PC / Na2Se).

[0054] The preparation method of UiO-66 in step (1) is the same as that in Example 1.

[0055] Example 3

[0056] A method for preparing a sodium metal negative electrode comprises the following steps:

[0057] (1) UiO-66 was placed in a porcelain boat, and then heated to 750°C at a heating rate of 5°C / min in a tube furnace in an argon atmosphere for 5 hours to obtain a solid (ZrO2@C). Then 150 mg of the obtained solid was dispersed in 60 mL of distilled water containing 6 mL of HF solution (HF 40% w / w) and kept ultrasonic for 30 minutes. After ultrasonic treatment, the solution was allowed to stand for 3 hours until the temperature dropped to room temperature, and then centrifuged again at 9000 rpm for 5 minutes, washed twice with methanol and once with distilled water, and finally heated in an oven at 80°C for 12 hours to obtain a porous carbon material (PC);

[0058] (2) The porous carbon material obtained in step (1) and selenium (Se) powder were mixed in a mass ratio of 1:5.5, placed in a porcelain boat, and then heated to 900°C in a tube furnace in an argon atmosphere at a heating rate of 5°C / min and calcined for 3h to obtain a selenium-porous carbon composite material (PC@Se);

[0059] (3) In an argon-filled glove box (O2 and H2O <0.1 ppm), sodium metal was heated at 250°C, and then the selenium-porous carbon composite material powder obtained in step (2) was slowly added, with the mass ratio of selenium-porous carbon composite material to molten sodium being 12:1. The mixture was stirred for 40 minutes, and the temperature was lowered to room temperature before rolling for 10 times to obtain the sodium metal anode (Na@PC / Na2Se).

[0060] The preparation method of UiO-66 in step (1) is the same as that in Example 1.

[0061] Example 4

[0062] The difference between the preparation method of the sodium metal negative electrode of this embodiment and that of embodiment 1 is that in step (2), the porous carbon material obtained in step (1) and selenium (Se) powder are mixed in a mass ratio of 1:3, and the rest is the same as that of embodiment 1 to obtain the sodium metal negative electrode of this embodiment.

[0063] Example 5

[0064] The preparation method of the sodium metal negative electrode of the present embodiment is different from that of the embodiment 1 in that, in the step (2), the porous carbon material obtained in the step (1) and the selenium (Se) powder are mixed in a mass ratio of 1:10, and the rest is the same as that of the embodiment 1 to obtain the sodium metal negative electrode of the present embodiment.

[0065] Comparative Example 1

[0066] The preparation method of the sodium metal negative electrode of this comparative example is: the porous carbon material (PC) prepared in Example 1 is directly compounded with molten sodium according to step (3) in Example 1 to obtain the negative electrode of this comparative example (Na@PC), that is, the preparation method of the sodium metal negative electrode of this comparative example does not include step (2) in Example 1.

[0067] Comparative Example 2

[0068] The preparation method of the sodium metal negative electrode of this comparative example is: directly compounding selenium powder and molten sodium according to step (3) in Example 1 to obtain the negative electrode of this comparative example (Na@Se), that is, the preparation method of the sodium metal negative electrode of this comparative example does not contain steps (1) and (2) in Example 1.

[0069] Performance Testing

[0070] The microstructures of PC and PC@Se prepared in Example 1 were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 As shown, from Figure 1It can be seen that the precursor UiO-66MOF is transformed from a smooth surface to an open porous channel surface with an average octahedral size of 100 nm after annealing. The cross-linking of the porous structure with selenium plays a key role in mitigating the uncontrollable growth of sodium dendrites during the plating / stripping process.

[0071] The Na@PC / Na2Se of the present invention was assembled into a symmetrical coin cell with a diameter of 10 mm for electrochemical testing. The electrolyte was a carbonate-based electrolyte (NaClO4 dissolved in ethyl methyl carbonate (EMC) and propylene carbonate (PC), with a volume ratio of PC: EMC = 1:1, NaClO4 1.0 M), the electrolyte dosage was 200 μL, and GF / D glass fiber was used as a separator. That is, a carbonate-based electrolyte was used to evaluate the sodium plating / stripping behavior of the sodium metal negative electrode Na@PC / Na2Se of Example 1 in a symmetrical cell, and compared with bare Na, Na@PC in Comparative Example 1, and Na@Se in Comparative Example 2. The results are as follows Figure 2 (a). Figure 2 As can be seen in (a), the Na@PC / Na2Se electrode exhibits excellent cycling stability at 1 mA cm -2 and 1 mAh cm -2 The polarization voltage was 42 mV for 1200 h under 4-volt ammonium ionization. In contrast, Na@PC, Na@Se, and bare Na only existed for 510 h, 520 h, and 215 h, with overpotentials of 49 mV, 77 mV, and 180 mV, respectively, leading to uncontrolled dendrite growth. Although the Na@Se and Na@PC electrodes effectively reduced the voltage polarization, after 510-520 h, these electrodes exhibited sporadic voltage behavior, causing fractal growth of dendrites. The long cycling performance of the Na@PC / Na2Se electrode indicates its excellent dual-layer stability in carbonate electrolytes.

[0072] The charge transfer resistance of Na@PC / Na2Se in symmetric cells was measured by EIS spectroscopy. Figure 2 (b)), the charge transfer resistance of the initial battery is higher than that of the battery after 2, 10, 50, 100, 200 and 300 cycles, respectively, which indicates that the in-situ SEI layer becomes more stable and strong after long-term cycling, indicating that the charge transfer resistance is smaller during the plating / stripping process. In order to further demonstrate the superiority of the Na@PC / Na2Se protective layer of Example 1, the cycling performance of the electrode of the present invention is compared with some previously reported electrodes, and the results are summarized in Figure 2 (c), where Cu 1.92S comes from the literature Advanced Functional Materials, 2018, 28, 1802282, SnS-G comes from the literature Energy & Environmental Science, 2021,14, 382-395, 3D-NVP comes from the literature Nano Energy, 2020, 70, 104479, Na-wood comes from the literature Nano Letters, 2017, 17, 3792-3797, Na2Te comes from the literature Advanced Materials, 2021, 33,2106353, Na / In / C comes from the literature Nano-Micro Letters, 2021, 14, 23, PhS2Na2 comes from the literature Angewandte Chemie International Edition, 2020, 59, 6596-6600, CNC / PEI comes from the literature Advanced Materials, 2022, 34, 2206367, this work is the present invention. Figure 2 As can be seen in (c), the electrode of the present invention exhibits excellent performance in terms of cycling stability, CE, and current density in carbonate-based electrolytes.

[0073] The sodium metal negative electrodes of Examples 4 and 5 were made into symmetrical coin cells for electrochemical testing. The electrolyte was the above-mentioned carbonate-based electrolyte (NaClO4 dissolved in ethyl methyl carbonate (EMC) and propylene carbonate (PC), with a volume ratio of PC: EMC = 1:1, NaClO4 1.0 M), the electrolyte dosage was 200 μL, and GF / D glass fiber was used as a separator. The cycling performance of the sodium metal negative electrodes of Examples 4 and 5 in carbonate-based electrolytes is shown in FIG. Figure 3 As shown, Figure 3 (a) The symmetrical cell of Example 4 at 1 mA cm −2 Up to 1mAh cm −2 Cycle performance diagram when Figure 3 (b) The symmetrical cell of Example 5 at 1 mA cm −2 Up to 1mAh cm −2 Cyclic performance diagram at capacity, from Figure 2 and Figure 3 It can be seen that the battery performance of Example 4 and Example 5 is inferior to that of Example 1. Figure 3 (a) shows that the battery capacity of Example 4 remains low and the charge transfer resistance is high, resulting in a short circuit, which may be due to the imbalance of the active material and the conductive matrix. Figure 3As can be seen in (b), the battery of Example 5 exhibits poor cycle stability and reduced electrochemical activity, indicating that excessive dilution of the active material has a negative impact on performance. In contrast, the battery of Example 1 produces better electrochemical results, and the ratio of the porous carbon material and selenium (Se) powder can ensure improved ionic and electronic conductivity.

[0074] The sodium metal negative electrode Na@PC / Na2Se of the present invention is further applied to a symmetrical battery formed by an ether electrolyte (1M sodium hexafluorophosphate (NaPF6) dissolved in diethylene glycol dimethyl ether), and the electrode of the present invention also exhibits excellent electrochemical performance. Cyclic performance is as follows Figure 4 (a) shown. Figure 4 (a) shows that the long cycling performance of the Na@PC / Na2Se||Na@PC / Na2Se of the present invention lasts for 8000 cycles even at 5 mA cm −2 The capacity per cycle was 2.5 mAh cm at a high current density of −2 .

[0075] Compared with the previously published studies on ether electrolytes, the electrodes of the present invention also showed excellent cycling performance, with the results showing Figure 4 (b), Zn / SnO2 comes from Chemical Engineering Journal, 2021, 404, 126469, PAN@ZIF comes from Journal of Power Sources, 2022, 551, 232165, N-CSs / Cu comes from Advanced Science, 2023, 10, 2206845, PAN comes from Advanced Energy Materials, 2020, 10, 2002308, Carbon paper comes from Energy Storage Materials, 2018, 15, 8-13, Porous Al comes from Nano Letters, 2017, 17, 5862-5868, Au-Na alloy comes from Advanced Materials, 2019, 31, 1807495, Na2Te@CF comes from Advanced Energy Materials, 2023, 13, 2204402, this work is the present invention.

[0076] In addition, bare Na, Na@Se of Comparative Example 1, and Na@PC of Comparative Example 2 in ether electrolyte symmetric cells show early voltage fluctuations, resulting in a decrease in the voltage at 4 mA cm -2The following generates 600, 2000, and 5000 cycles respectively, such as Figure 5 shown.

[0077] With NVP (Na3V2(PO4)3) as the positive electrode and Na@PC / Na2Se of the present invention as the negative electrode, the full cell Na@PC / Na2Se||NVP was assembled for electrochemical performance testing. The preparation method of the positive electrode sheet is as follows: in 1-methyl-2-pyrrolidone (NMP) solvent, NVP, conductive carbon (Super P) and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1 to obtain a slurry, which is coated on aluminum foil and then vacuum dried at 65°C. The electrode is then cut into a disc shape and the mass loading of each electrode is kept at 3.0 mg cm -2 The electrolyte is an ether electrolyte (1M sodium hexafluorophosphate (NaPF6) dissolved in diethylene glycol dimethyl ether), the electrolyte dosage is 200μL, and GF / D glass fiber is the diaphragm; the test results are as follows Figure 6 As shown. Figure 6 It can be seen that compared with the bare Na||NVP battery, the Na@PC / Na2Se||NVP of the present invention has excellent electrochemical performance. Figure 6 (a) shows that Na@PC / Na2Se||NVP exhibits 131 mAh g at 5C current density. -1 The superior initial capacity of Na||NVP lasted for 2400 cycles. In comparison, Na||NVP showed 109 mAh g -1 , which was cycled only 900 times. More importantly, at high current densities, especially at 10C and 20C, the improved full cell maintained its superior rate performance. Figure 6 As can be seen in (b), even at a high current density of 20C, the Na@PC / Na2Se||NVP full cell of the present invention shows 106 mAh g -1 , and lasted to 85 mAh g after 4000 cycles. -1 , while the bare Na||NVP full cell initially showed 90 mAh g -1 , and a short circuit occurred after 910 cycles.

[0078] The Na@PC in Comparative Example 1 and the Na@Se in Comparative Example 2 were assembled into the above-mentioned full cell to observe the nucleation overpotential and compared with bare Na and Example 1. The results are as follows Figure 7 (a) shows that during the initial electroplating process, the difference between the stable voltage platform and the minimum voltage drop can well characterize the nucleation overpotential. Figure 7As can be seen from (a), the nucleation overpotential of the Na@PC / Na2Se (35 mV) of the present invention is lower than that of the bare Na, Na@Se and Na@PC surfaces, indicating that the Na ions adsorbed on the PC / Na2Se protective skeleton are more stable than those on the bare Na, Na@PC and Na@Se surfaces, and have a higher affinity for Na ions. The prepared asymmetric battery was further tested for the average Coulombic efficiency CE of 200 cycles, and the test results are shown in Figure 2. Figure 7 (b) The Na@PC / Na2Se||Cu of Example 1 at 1 mA cm −2 The results show that the CE is very stable when the PC@Se@SiO2 ...

[0079] The Na@PC / Na2Se scaffold of the present invention can effectively form a stable in-situ artificial solid electrolyte interface SEI layer and inhibit the growth of Na dendrites after long-term cycling. In-situ scanning electron microscopy and in-situ optical microscopy were used to observe the surface of the Na@PC / Na2Se and bare Na electrodes in Example 1 during the cycling process of the ether-based electrolyte symmetric battery to explore the surface reaction mechanism. The test results are as follows: Figure 8 At 1 mA cm −2 Up to 0.5 mAhcm −2 Under the condition of 100 cycles, the surface morphology of the exposed Na surface was studied by scanning electron microscope (SEM). The results showed that a large number of spots and cracks appeared on the exposed Na surface. Figure 8 (ad)). In contrast, the Na@PC / Na2Se electrode maintains a relatively flat and smooth surface morphology ( Figure 8 (ef)), and no Na dendrites were formed during repeated electroplating ( Figure 8 (gh)). In situ optical microscopy was used to observe the symmetric cell through transparent quartz filled with alcohol-ether-based electrolyte and to confirm the advantage of the Na2Se protective layer during in situ Na deposition. Initially, both bare Na and Na@PC / Na2Se electrodes showed smooth surfaces during Na deposition. As the Na deposition time increased, non-uniform nucleation behavior appeared on the surface of the exposed Na electrode, and these dendrites began to grow continuously after 60 minutes ( Figure 8 (i)). As expected, the Na@PC / Na2Se electrode exhibits uniform deposition behavior and maintains no dendrite formation on the electrode surface throughout the deposition process ( Figure 8 (j)).

[0080] The schematic diagram of the structure of the PC@Se composite material of the present invention and the schematic diagram of the principle of in-situ artificial SEI layer modification of Na electrode are shown in Fig. 9 As shown. Combined with the performance tests, it can be seen that the present invention synthesized a three-dimensional porous carbon scaffold @ selenium (PC@Se), and the 3D scaffold serves as a dual-functional hybrid interface layer on the Na metal surface during a simple heating injection and rolling / folding process. In the newly modified Na@PC / Na2Se electrode, the lower layer contains PC that can directly contact the metal surface, and the upper layer contains an in-situ artificial Na2Se layer. During the initial electroplating process, the in-situ Na2Se artificial SEI layer can provide a more uniform and mechanically stable host for the controlled growth of Na metal. The PC as a supported 3D matrix on the Na metal surface can further accommodate the volume expansion of the interface and promote the reversibility of the Na2Se SEI layer during repeated plating / stripping. This synergistic effect makes Na + The Na@PC / Na2Se carbonates in Na metal symmetric cells (1200 h, 1.0 mA cm -2 ) and ether (8000 h, 5.0 mA cm -2 ) alkaline electrolytes. Finally, the long cycle performance of the Na@PC / Na2Se||NVP full cell was demonstrated using an ether-based electrolyte. -1 ) After 4000 cycles, it showed 85 mAh g -1 .

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a sodium metal negative electrode, characterized in that: The following steps are involved: (1) mixing the solid obtained by high-temperature calcination of UiO-66 with a hydrofluoric acid solution, standing, and drying to obtain a porous carbon material; (2) mixing the porous carbon material obtained in step (1) with selenium powder, and calcining at high temperature to obtain a selenium-porous carbon composite material; (3) The selenium-porous carbon composite material obtained in step (2) is uniformly mixed with molten sodium, and the mixture is rolled after cooling to obtain the sodium metal negative electrode.

2. The method for preparing a sodium metal negative electrode according to claim 1, characterized in that: In the step (1), the high temperature calcination temperature is 750°C-850°C, and the time is 3h-5h.

3. The method for preparing a sodium metal negative electrode according to claim 1, characterized in that: In the step (1), the mass volume ratio of the solid to the hydrofluoric acid solution is (50-150) mg: (20-60) mL; and the mass percentage of hydrofluoric acid in the hydrofluoric acid solution is 5%-7%.

4. The method for preparing a sodium metal negative electrode according to claim 1, characterized in that: In the step (2), the mass ratio of the porous carbon material to the selenium powder is 1:(3-10).

5. The method for preparing a sodium metal negative electrode according to claim 4, characterized in that: In the step (2), the mass ratio of the porous carbon material to the selenium powder is 1:(4.5-5.5).

6. The method for preparing a sodium metal negative electrode according to claim 1, characterized in that: In the step (2), the high temperature calcination is carried out at a temperature of 800°C-900°C and for a time of 3h-5h.

7. The method for preparing a sodium metal negative electrode according to claim 1, characterized in that: In the step (3), the mass ratio of the selenium-porous carbon composite material to the molten sodium is (8-12):

1.

8. The method for preparing a sodium metal negative electrode according to claim 1, characterized in that: Satisfy at least one of the following: (1) In step (1), the preparation method of UiO-66 comprises the following steps: dissolving zirconium chloride, terephthalic acid and acetic acid in dimethylformamide, and then performing a hydrothermal reaction to obtain UiO-66; (2) In step (1), the standing time is 1 h to 3 h; (3) In step (1) and step (2), the high-temperature calcination is carried out in an inert atmosphere, and the inert atmosphere includes argon; (4) In step (3), the temperature of the molten sodium is 200°C-300°C; (5) In step (3), the rolling is performed 5 to 15 times.

9. The sodium metal negative electrode prepared by the method for preparing the sodium metal negative electrode according to any one of claims 1 to 8.

10. A sodium metal battery, characterized in that: Comprising the sodium metal negative electrode as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery negative electrode material

    CN113912023A

  • Preparation method and application of sodium ion battery negative electrode energy storage material

    CN115132980A